Effect of Vitamin D Supplementation on Recurrent Wheezing in Black Infants Who Were Born Preterm: The D-Wheeze Randomized Clinical Trial - Hibbs, Anna Maria (JAMA, 2018)
IMPORTANCE: Black infants born preterm face high rates of recurrent wheezing throughout infancy. Vitamin D supplementation has the potential to positively or negatively affect wheezing through modulation of the pulmonary and immune systems. OBJECTIVE: To assess the effectiveness of 2 vitamin D dosing strategies in preventing recurrent wheezing. DESIGN, SETTING, AND PARTICIPANTS: A randomized clinical trial enrolled 300 black infants born at 28 to 36 weeks’ gestation between January 2013 and January 2016 at 4 sites in the United States, and followed them up through March 2017. Randomization was stratified by site and maternal milk exposure. INTERVENTIONS: Patients were enrolled prior to discharge from the neonatal intensive care unit or newborn nursery and received open-label multivitamin until they were consuming 200 IU/d of cholecalciferol from formula or fortifier added to human milk, after which they received either 400 IU/d of cholecalciferol until 6 months of age adjusted for prematurity (sustained supplementation) or placebo (diet-limited supplementation). One-hundred fifty three infants were randomized to the sustained group, and 147 were randomized to the diet-limited group. MAIN OUTCOMES AND MEASURES: Recurrent wheezing by 12 months’ adjusted age was the primary outcome. RESULTS: Among 300 patients who were randomized (mean gestational age, 33 weeks; median birth weight, 1.9 kg), 277 (92.3%) completed the trial. Recurrent wheezing was experienced by 31.1% of infants in the sustained supplementation group and 41.8% of infants in the diet-limited supplementation group (difference, −10.7% [95% CI, −27.4% to −2.9%]; relative risk, 0.66 [95% CI, 0.47 to 0.94]). Upper and lower respiratory tract infections were among the most commonly reported adverse events. Upper respiratory infections were experienced by 84 of 153 infants (54.9%) in the sustained group and 83 of 147 infants (56.5%) in the diet-limited group (difference, −1.6% [95% CI, −17.1% to 7.0%]). Lower respiratory infections were experienced by 33 of 153 infants (21.6%) in the sustained group and 37 of 147 infants (25.2%) in the diet-limited group (difference, −3.6% [95% CI, −16.4% to 4.4%]). CONCLUSIONS AND RELEVANCE: Among black infants born preterm, sustained supplementation with vitamin D, compared with diet-limited supplementation, resulted in a reduced risk of recurrent wheezing by 12 months’ adjusted age. Future research is needed to better understand the mechanisms and longer-term effects of vitamin D supplementation on wheezing in children born preterm. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT01601847